La información empírica en la investigación de la Sociología del Derecho (Società e diritti, 2023)
This article discusses the concept of data and scientific data. Measurement and quantification of the variable. The data matrix: relationship between unit of analysis, variable and data. Data in socio-legal research. Sample: types, size and selection. Data collection techniques: observation, interview, questionnaire and content analysis. Data systematization.